Tick-borne diseases in Egypt: A one health perspective - Abdelbaset, Abdelbaset Eweda; Nonaka, Nariaki; Nakao, Ryo (One health, 2022)
Ticks are important arthropod vectors that transmit pathogens to humans and animals. Owing to favourable climatic and environmental conditions, along with animal importation from neighbouring countries, ticks and tick-borne diseases (TBDs) are widespread in Egyptian localities. Here, we review the current knowledge on the epidemiology of TBDs in Egypt in light of the One Health paradigm. Five scientific databases, including “Web of Science”, “Scopus”, “PubMed”, “Science Direct”, and “Google Scholar”, were searched for articles describing TBDs in Egypt. A total of 18 TBDs have been reported in humans and animals, including three protozoal diseases (babesiosis, theileriosis, and hepatozoonosis), 12 bacterial diseases (anaplasmosis, ehrlichiosis, Lyme borreliosis, bovine borreliosis, tick-borne relapsing fever, Mediterranean spotted fever, African tick-borne fever, lymphangitis-associated rickettsiosis, bartonellosis, tularaemia, Q fever, and aegyptianellosis), and three viral diseases (Crimean-Congo haemorrhagic fever, Alkhurma haemorrhagic fever, and Lumpy skin disease). Despite the circulation of zoonotic tick-borne pathogens among livestock and tick vectors, human infections have been overlooked and are potentially limited to infer the actual communicable disease burden. Therefore, facility-based surveillance of TBDs, combined with capacity building for laboratory diagnostics in healthcare facilities, is urgently required to improve diagnosis and inform policy-making in disease prevention. Additionally, collaboration between expert researchers from various disciplines (physicians, biologists, acarologists, and veterinarians) is required to develop advanced research projects to control ticks and TBDs. Considering that domestic livestock is integral to many Egyptian households, comprehensive epidemiological studies on TBDs should assess all disease contributors, including vertebrate hosts (animals, humans, and rodents) and ticks in the same ecological region, for better assessment of disease burden. Additionally, upscaling of border inspections of imported animals is required to stop crossover movements of ticks and TBDs. •Tick-borne diseases are widespread in Egypt.•Several economically relevant diseases have been reported in livestock.•Zoonotic tick-borne diseases are neglected and underestimated.•The current review suggests implementation of the One Health approach.•Standardisation of measures for animal importation is required.